Paris in the present tense - Helprin, Mark (New York, NY : Overlook Press, 2017)
When faced with a series of challenges to his principles, livelihood, and home, Julesa seventy-four-year-old maître at Paris-Sorbonne, cellist, widow, veteran of the war in Algeria, and child of the Holocaustmust confront his complex past and find a way forward.
Keywords: Terminally ill children -- Fiction; Families -- Fiction; Terminally ill children -- Fiction; Family life -- Fiction; Paris (France) -- Fiction; Paris (France) -- Fiction